2019
DOI: 10.1021/acsomega.9b02615
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and Antibacterial Properties of PEGylated Zinc Oxide Nanoparticles Dispersed in Peritoneal Dialysis Fluid

Abstract: Owing to the peculiar broad-spectrum antimicrobial activities of zinc oxide nanoparticles (ZnO NPs), we envisaged their use to treat bacterial/mycobacterial/fungal infections during peritoneal dialysis (PD) of end-stage renal failure patients. However, a recent study from our lab showed that ZnO-NPs cannot be employed for the same in their naked form owing to their rapid agglomeration. Also, the naked ZnO-NPs showed strong interaction with organic acids present in the PD fluid (i.e., lactate and citrate presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 41 publications
2
23
0
Order By: Relevance
“…It was previously reported that surface coating of ZnONps could prevent their interactions with biological fluid. However, Pranjali et al (2019) found that PEGylated ZnONps strongly bind and interact with peritoneal dialysis (PD) fluid, lactic and citric acids leading to agglomeration. In addition, a drastic decrease in the bacterial inhibition effect was observed for both the ZnONps and the PEG-coated ZnONps dispersed in biological fluid.…”
Section: Metallic and Metal Oxide Nanoparticles Are Promising Antibacterial Agentsmentioning
confidence: 99%
“…It was previously reported that surface coating of ZnONps could prevent their interactions with biological fluid. However, Pranjali et al (2019) found that PEGylated ZnONps strongly bind and interact with peritoneal dialysis (PD) fluid, lactic and citric acids leading to agglomeration. In addition, a drastic decrease in the bacterial inhibition effect was observed for both the ZnONps and the PEG-coated ZnONps dispersed in biological fluid.…”
Section: Metallic and Metal Oxide Nanoparticles Are Promising Antibacterial Agentsmentioning
confidence: 99%
“…Anti-bacterial effects on Gram-negative and Gram-positive bacteria have been demonstrated in vitro [142,145,146]. More recently, it was shown that polyethylenglycol-encapsulated ZnO interacts strongly with the citric acid and lactic acid, leading to a bacterial inhibition effect against S. aureus and E. coli [142,154], and S. mutans and Lactobacillus in dental plaque [155]. The anti-microbial effects of ZnO are similar to Ag NPs because the smaller the NPs are, the larger the surface area becomes.…”
Section: Zinc Oxide Nanoparticlesmentioning
confidence: 99%
“…One of the most commonly used approaches consists of grafting PEG polymer onto the surface to create an anti-infection effect. [74] Although PEG coating itself has no bactericidal nature, its intrinsic nonfouling features decrease the bacterial interaction with its surfaces. Different approaches can be followed in order to attach different hydrophilic polymers to the biomaterials surfaces, either physical or chemical modification has been used as covalent grafting or plasma polymerization as more representative.…”
Section: Polyethylene Glycol (Peg) Coatingsmentioning
confidence: 99%